Epitope mapping of epidermal growth factor receptor (EGFR) monoclonal antibody and induction of growth-inhibitory polyclonal antibodies by vaccination with EGFR mimotope. (October 2014) - Navari, Mohsen; Zare, Mehrak; Javanmardi, Masoud; Asadi-Ghalehni, Majid; Modjtahedi, Helmout; Rasaee, Mohammad Javed
Abstract One of the proposed approaches in cancer therapy is to induce and direct the patient's own immune system against cancer cells. In this study, we determined the epitope mapping of the rat anti-human epidermal growth factor receptor (EGFR) monoclonal antibody ICR-62 using a phage display of random peptide library and identified a 12 amino acids peptide, which was recognized as a mimotope. The peptide was synthesized and conjugated to bovine serum albumin (BSA) as carrier protein (P-BSA). We have shown that ICR-62 can react specifically with P-BSA as well as native EGFR. Two rabbits were immunized either by BSA or P-BSA and the rabbits IgGs were purified and examined for binding to the antigens, mimotope and the EGFR protein purified from the EGFR overexpressing A431 cell line. We showed that the rabbit IgG generated against the mimotope is capable of inhibiting the growth of A431 cells by 15%, but does not have any effect on the growth of EGFR-negative MDA-MB-453 cell line in vitro. Our results support the need for further investigations on the potential of vaccination with either mimotope of the EGFR or epitope displayed on the surface of phage particles for use in active immunotherapy of cancer.